Longitudinal associations of physical activity and sedentary time with cardiometabolic risk factors in children. (23rd October 2018) - Väistö, Juuso; Haapala, Eero A.; Viitasalo, Anna; Schnurr, Theresia M.; Kilpeläinen, Tuomas O.; Karjalainen, Panu; Westgate, Kate; Lakka, Hanna‐Maaria; Laaksonen, David E.; Ekelund, Ulf; Brage, Søren; Lakka, Timo A.
Abstract : Background: There are few prospective studies on the associations of changes in objectively measured vigorous physical activity (VPA∆ ), moderate‐to‐vigorous physical activity (MVPA∆ ), light physical activity (LPA∆ ), and sedentary time (ST∆ ) with changes in cardiometabolic risk factors (∆ ) in children. We therefore investigated these relationships among children. Methods: The participants were a population sample of 258 children aged 6‐8 years followed for 2 years. We assessed PA and ST by a combined heart rate and movement sensor; computed continuous age‐ and sex‐adjusted z ‐scores for waist circumference, blood pressure, and fasting insulin, glucose, triglycerides, and high‐density lipoprotein (HDL) cholesterol; and constructed a cardiometabolic risk score (CRS) of these risk factors. Data were analyzed using linear regression models adjusted for age, sex, the explanatory and outcome variables at baseline, and puberty. Results: VPA∆ associated inversely with CRS∆ ( β = −0.209, P = 0.001), body fat percentage (BF%)∆ ( β = −0.244, P = 0.001), insulin∆ ( β = −0.220, P = 0.001), and triglycerides∆ ( β = −0.164, P = 0.012) and directly with HDL cholesterol∆ ( β = 0.159, P = 0.023). MVPA∆ associated inversely with CRS∆ ( β = −0.178, P = 0.012), BF%∆ ( β = −0.298, P = <0.001), and insulin∆ ( β = −0.213, P = 0.006) and directly with HDL cholesterol∆ ( β = 0.184, P = 0.022). LPA∆ only associated negatively with CRS∆ ( β = −0.163, P = 0.032). ST∆ associated directly with CRS∆ ( β = 0.218, P = 0.003), BF%∆ ( β = 0.212, P = 0.016), and insulin∆ ( β = 0.159, P = 0.049). Conclusions: Increased VPA and MVPA and decreased ST were associated with reduced overall cardiometabolic risk and major individual risk factors. Change in LPA had weaker associations with changes in these cardiometabolic risk factors. Our findings suggest that increasing at least moderate‐intensity PA and decreasing ST decrease cardiometabolic risk in children.